2003
DOI: 10.5194/acp-3-259-2003
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for measuring canonical tracer relationships in the stratosphere

Abstract: Abstract.A high-resolution simulation of stratospheric long-lived trace gases is subsampled in ways resembling various commonly used measurement platforms. The resulting measurements are analyzed with respect to whether they allow an accurate determination of stratospheric tracer relationships, as a prerequisite for a quantification of mixing processes from them. By varying the simulated locations, frequencies, and, in the case of satellite data, accuracies of the measurements we determine minimal requirements… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…11a). The asymmetry of the midlatitude tracer-tracer correlation functions measured in both hemispheres is discussed in the literature (e.g., Morgenstern and Pyle, 2003).…”
Section: Tracer-tracer Relationships In the ∆χ N 2 O Parametrizationmentioning
confidence: 99%
“…11a). The asymmetry of the midlatitude tracer-tracer correlation functions measured in both hemispheres is discussed in the literature (e.g., Morgenstern and Pyle, 2003).…”
Section: Tracer-tracer Relationships In the ∆χ N 2 O Parametrizationmentioning
confidence: 99%
“…The uncertainties and footprint of HALOE data are larger than for in situ data. Morgenstern and Pyle (2003) assessed the effects of these factors on the ability to distinguish different tracer correlations across the stratospheric polar vortex. They concluded that although HALOE might be inappropriate for localized studies, for low-resolution studies the redundancy in the data should allow the accurate differentiation of tracer correlations.…”
Section: The Haloe Datasetmentioning
confidence: 99%